Design study and cost assessment of straight, zigzag, S-shape, and OSF PCHEs for a FLiNaK–SCO2 Secondary Heat Exchanger in FHRs. (August 2016) - Kim, In Hun; Zhang, Xiaoqin; Christensen, Richard; Sun, Xiaodong
Highlights: Various PCHE channel configurations were investigated for a SHX in FHRs. Thermal-hydraulics, mechanical aspect, and corrosion rate were considered for the design. Designs of 20-MW FLiNaK–SCO2 SHX for the FHR were proposed. Abstract: This study focused on designing a cost-effective heat exchanger for a 20-MW FLiNaK–SCO2 Secondary Heat Exchanger in Fluoride salt-cooled High-temperature Reactors. Specific Printed Circuit Heat Exchanger geometries were investigated for those cases where Fanning factor and Nusselt number correlations were available. Straight, S-shape, Offset Strip Fin, and zigzag 52° channels were considered for the SCO2 side while straight, zigzag 15°, rectangle OSF 7.565 mm, and rectangle OSF 2.40 mm channels were considered for the FLiNaK side. Thermal-hydraulics, mechanical aspects, and corrosion rate were taken into account. A cost analysis was performed to combine the effects of heat transfer performance and pressure drop in heat exchangers. Single banking and double banking were also considered. Finally, the best PCHE channel configurations on SCO2 and FLiNaK sides were proposed.